Analysis of the Benefits of Wokee Application Information Technology Investment - Dewi Novita Putri; I Putu Agus Swastika; Ni Made Estiyanti (STKIP Yapis Dompu, 2023)
Information Technology investment is an indispensable thing for companies. Information technology in the company can support progress in decision making and provide a competitive advantage for companies to compete with competitors, both those who come in the same industry or are different from competing with competitors globally. The banking sector is one of the sectors affected by the development of information and communication technology. The purpose of this study was to determine the effect of Wokee application technology investment in PT. Bank KB Bukopin TBK. The identification of the investment benefits is carried out using a qualitative descriptive approach, cost benefit analysis (CBA) analysis method, and Ranti's Generic IS/IT Business Value method.